2020
DOI: 10.1186/s12302-020-00404-8
|View full text |Cite
|
Sign up to set email alerts
|

Selection and application of trophic magnification factors for priority substances to normalize freshwater fish monitoring data under the European Water Framework Directive: a case study

Abstract: Background The European Water Framework Directive (WFD) requires the monitoring of biota—preferably fish—to check the compliance of tissue concentrations of priority substances (PS) against substance-specific environmental quality standards (EQSs). In monitoring programs, different fish species are covered, which often are secondary consumers with a trophic level (TL) of about 3. For harmonization, a normalization of monitoring data to a common trophic level is proposed, i.e., TL 4 (predatory f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 50 publications
(137 reference statements)
1
3
1
Order By: Relevance
“…The TMFs in the present study were compared to those of other studies on freshwater ecosystems, and were higher than those reported by Loi et al [54] for PFOS (TMF = 1.3) and lower than those for PFUnDA (TMF = 1.7), although the general trend of biomagnification was comparable to the present study. Furthermore, the TMF PFOS calculated in the present study is in line with other European studies on lake and river food chains as reported by Rüdel et al [64]. On the other hand, Lescord et al [53] reported a negative relation between accumulation and trophic level for PFOS, PFNA and PFUnDA in a foodweb from the high Arctic.…”
Section: Pfas Bioaccumulation Magnification and Dilutionsupporting
confidence: 92%
See 2 more Smart Citations
“…The TMFs in the present study were compared to those of other studies on freshwater ecosystems, and were higher than those reported by Loi et al [54] for PFOS (TMF = 1.3) and lower than those for PFUnDA (TMF = 1.7), although the general trend of biomagnification was comparable to the present study. Furthermore, the TMF PFOS calculated in the present study is in line with other European studies on lake and river food chains as reported by Rüdel et al [64]. On the other hand, Lescord et al [53] reported a negative relation between accumulation and trophic level for PFOS, PFNA and PFUnDA in a foodweb from the high Arctic.…”
Section: Pfas Bioaccumulation Magnification and Dilutionsupporting
confidence: 92%
“…For eel and perch, respectively, 44% and 58% of sampling locations exceeded the EQS biota, hh , indicating potential health risks to the food web and to top predators (including humans) through fish consumption. In a German monitoring study, PFOS was above the EQS biota,hh in 33% of the locations in perch muscle [64,65]. However, the current EQS biota, hh is based on the previous EFSA tolerable daily intake (TDI) value for PFOS of 150 ng/kg body weight, which can be converted to 10.5 µg per day considering a 70 kg person [26,56].…”
Section: Ecological Health Riskmentioning
confidence: 99%
See 1 more Smart Citation
“…This was unexpected, as CB180 is the highest chlorinated congener in this study. However, the TMF for CB180 in this study is higher than reported globally, where Rüdel et al, (2020) reported a range of 1.2 -4.6 in pelagic and benthopelagic food webs in Italy, Norway, Finland and Canada; reported a TMF of 1.06 from a food web composed of invertebrates and fish in Ulson Bay, Korea. The value for CB52 is also much higher than reported globally.…”
Section: J O U R N a L P R E -P R O O Fcontrasting
confidence: 84%
“…This requires a numerical TMF value rather than an answer to the question, whether the TMF is above or below 1. A recent analysis illustrated challenges associated with the normalization approach which may result in an overestimation of TMF corrected biota concentrations [82].…”
Section: Evaluation Under Aspects Of the Wfdmentioning
confidence: 99%